Oracle utilities : pocket reference - Mishra, Sanjay (O'Reilly Media, Inc., 2004)
The Oracle Utilities Pocket Reference is a handy, quick-reference guide to the multitude of Oracle utilities that database administrators (DBAs) use every hour of every day. As the undisputed leader among database products, Oracle is grasped conceptually by most DBAs. However, they understandably may not recall the specific utility to use for a given task, and, more commonly, won't in many cases remember the syntax to use. And that's exactly what the Oracle Utilities Pocket Reference supplies--the syntax and options for whatever utility a DBA needs to perform a given task. Some of the utilities documented in this guide include: SQL*Loader, for loading data expdp and exp for exporting data to another database oradebug for use in troubleshooting loadjava and dropjava for loading and unloading Java programs Packed with information in an easy-to-read format, this valuable resource is ideal for any experienced DBA. Even database programmers who deal with Oracle will truly appreciate having the Oracle Utilities Pocket Reference close at hand. Authored by Sanjay Mishra, a foremost authority on Oracle systems, this convenient and compact guide is focused and to-the-point, eliminating any potential guesswork or difficult memorization. The Oracle Utilities Pocket Reference is part of the strong-selling collection of O'Reilly "pocket reference" books